THE MULTIFACETED WORLD OF PRONOUNS: A LINGUISTIC EXPLORATION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article provides a foundational overview of English pronouns, intended for students of linguistics and language enthusiasts. It aims to clarify their grammatical functions and classifications, acknowledging the ongoing evolution of their usage in contemporary discourse.